Factors impacting learners’ proficiency in the Heritage Language Shanghainese - Chen, C (2022)
This study aims to better understand the current status of Shanghainese, a Chinese Heritage Language (CHL), and to help its preservation. It explores learners’ usage patterns and their proficiency level in Shanghainese. It also investigates what factors impact the learners’ Shanghainese competence by looking into the relationship between learners’ HL proficiency and their attitudes and beliefs towards the dialect, engagement in dialect-related cultural activities, demographic backgrounds, as well as their home and community language environment. Most previous studies did not specify a regional dialect when researching CHLs, only employed relatively simple statistical analysis, relied on participants’ self-report and focused on a very narrow range of variables that could impact the CHL proficiency. This study designed a questionnaire and a Shanghainese proficiency test to collect speaker information among 187 Shanghainese teenagers between Year 10 (16 years old) and Year 12 (18 years old) from five different high schools in Shanghai. The results showed that the participants generally preferred speaking Mandarin Chinese to Shanghainese in varied scenarios. Their self-perceived and tested Shanghainese proficiency were significantly positively correlated. The participants with a more positive attitude towards Shanghainese, more frequent attendance to dialect-related cultural activities, a more local demographic background, as well as a more dialect-oriented home language environment would have a higher competence level in the dialect Shanghainese. Implications for future research are also provided in this study.